Typical value ranges and signal patterns in patients with neurogenic bladder: Quality control in urodynamics using an air‐charged catheter system. Issue 1 (2nd October 2022) - Deng, Han; Liao, Limin; Wu, Juan; Li, Xing; Pang, Dongqing; Liu, Qinggang; Wang, Xuesheng; Li, Xunhua; Liang, Ya'nan; Zhou, Zhonghan; Luo, Runtian; He, Panqi
Abstract: Purpose: To establish typical value ranges (TVRs) of the air‐charged catheter (ACC) system, and analyze the typical signal patterns (TSPs) of cough under different bladder volumes for quality control of a urodynamic study using the ACC system. Materials and Methods: The urodynamic traces of 1977 patients with neurogenic bladder (NB) were analyzed for intravesical pressure (pves ), abdominal pressure (pabd ), and detrusor pressure (pdet ) in the cough test at our center from July 2017 to December 2021. The pdet cough signals were described and classified. The pdet cough signal patterns in different bladder volumes and postures were analyzed. Results: The 50% range of the initial resting pves, pabd, and pdet in the supine and sitting positions were 7–15, 7–14, and 0–0 cmH2 O, and 24–33, 24–33, and 0–0 cmH2 O, respectively. The cough amplitudes for pves and pabd were similar in the 50% range, as follows: 10–27 and 8–25 cmH2 O in the supine position, respectively; and 18–43 and 17–40 cmH2 O in the sitting position, respectively. The cough amplitude of pves and pabd was not related to bladder volume ( p > 0.05). The cough spikes of pdet were divided into three types: type I, in which pdet has a minimal change (<5 cmH2 O); type II, a monophasic cough spike, in which could be a positive (IIa, ≥5 cmH2 O) or negative spike (IIb, ≥5 cmH2 O); and type III, a biphasic spike, in which could be a positive‐to‐negative biphasic (IIIa) or negative‐to‐positive spike (IIIb). Under different bladder volumes, the cough signals of pdet were all expressed as type I, II, or III, and the cough signals were unrelated to bladder volume ( p > 0.05). Conclusions: TVRs of the initial resting state in patients with NB were established to provide guidance for quantitative quality control of the ACC system. The TSPs of the pdet cough signal under different bladder volume and posture were described, which could be used for qualitative quality control of the ACC system.